PENDEKATAN ADMINISTRASI PUBLIK DALAM MEMPROMOSIKAN INISIASI MENYUSUI DINI (IMD) PADA PELAYANAN KESEHATAN - Ningrum, Monica Ayu; Janah , Samrotul; Darmawan , Zikri Dwi; Dewi , Maya Puspita (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The early initiation of breastfeeding (IMD) is universally recognized as the optimal method of infant nutrition and plays a crucial role in promoting both maternal and child health. Early initiation of breastfeeding (IMD)—the practice of beginning breastfeeding within the first hour after birth—has been shown to provide essential health benefits, including boosting the infant’s immune system and fostering bonding between mother and child. The World Health Organization (WHO) and UNICEF emphasize that early initiation is critical for reducing infant mortality and morbidity, improving cognitive development, and preventing diseases such as respiratory infections and diarrhea. While the benefits of early breastfeeding initiation are well documented, significant barriers remain in its widespread adoption. These barriers are often systemic, ranging from inadequate healthcare infrastructure to cultural and societal attitudes. Public administration, which involves the design and implementation of policies, plays a pivotal role in overcoming these obstacles. This article explores how public administration approaches can promote EBI within healthcare systems, focusing on policy development, healthcare provider training, and public awareness campaigns.